Sustaining substance use recovery housing for people taking medications for opioid use disorder: diverse funding, strategic partnerships, and charging rent - Zoschke, I. Niles; Gallardo, Kathryn R.; Gillespie, Danielle; Stewart, Hannah L. N.; Rodriguez, Serena A.; McCurdy, Sheryl A.; Wilkerson, J. Michael (Frontiers in Public Health, 2025)
IntroductionOpioid use disorder is a U.S. epidemic, and recovery housing plays a critical role by providing stable, supportive environments that promote long-term recovery. However, little is known about the sustainability of recovery homes, particularly those serving people taking medications for opioid use disorder.MethodsWe applied thematic analysis to interviews with 29 staff and operators from 10 recovery homes serving people taking medications for opioid use disorder across five Texas cities.ResultsOperators relied on diverse funding sources, leveraged strategic partnerships and professional certifications, and planned to charge rent when public funding ended. Staff and operators balanced financial sustainability with maintaining quality services.DiscussionFindings offer guidance for sustaining recovery homes that support medications for opioid use disorder. Recovery home operators can leverage professional networks, strengthen partnerships, rely on diverse funding sources, and reduce operational costs to sustain services. Policymakers can further support sustainability by establishing long-term funding mechanisms and reducing financial barriers to professional certification, ultimately improving service quality and access.